1994
DOI: 10.1002/aoc.590080416
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of arsenic by anaerobic microbial consortia isolated from lake sediment

Abstract: Anaerobic enrichment cultures, isolated from arsenic-contaminated lake sediment in the Canadian sub-arctic and grown in five selective media, methylated arsenatef arsenite to produce mono-, di-and tri-methyl arsenicals. The extent of methylation and methylarsenic species produced varied with the type of enrichment. Iron-reducing, manganese-reducing, sulfate-reducing and broadspectrum anaerobic heterotrophic mixed cultures all produced methylarsenicals. Sulfate-reducing cultures produced higher concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 12 publications
3
26
0
Order By: Relevance
“…Among several anaerobic As methylating microbes isolated from an As-contaminated lake sediment, sulfur-reducing microbes were found to possess the highest ability to methylate As. 51 The GeoChip assay ( Figure 2) revealed considerable diversity in the arsM sequences present in the six soils studied. Similarly, Jia et al 36 reported that microbes containing arsM genes were phylogenetically diverse in an As-contaminated paddy soil.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Among several anaerobic As methylating microbes isolated from an As-contaminated lake sediment, sulfur-reducing microbes were found to possess the highest ability to methylate As. 51 The GeoChip assay ( Figure 2) revealed considerable diversity in the arsM sequences present in the six soils studied. Similarly, Jia et al 36 reported that microbes containing arsM genes were phylogenetically diverse in an As-contaminated paddy soil.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Enrichment cultures of anaerobes isolated from an arseniccontaminated lake in the Canadian sub-Arctic region with five selective media showed extensive formation of methylarsenicals (30). Anaerobic oligotrophs were most active, producing a high proportion of dimethylarsinate.…”
Section: Role Of Anaerobic Microorganismsmentioning
confidence: 99%
“…Tentative links have also been drawn between sulfate-reducing bacteria (SRB) and arsenic biomethylation. Bright et al 30 showed that sulfatereducing as well as fermentative and/or methanogenic cultures enriched from lake sediments produced more methylated arsenic than iron-or manganese-reducing cultures. Mikutta and Rothwell 31 showed that 82% of the As in a sulfate-and Asimpacted peat bog was present as organoarsenic species, and Zeng et al 32 showed that the abundance of methylated As in the roots of a ginseng plant increased 263% following soil amendment with sulfate (SO 4 …”
Section: ■ Introductionmentioning
confidence: 99%